Isolasi dan Identifikasi Jamur Pada Buah Cabai Rawit (Capsicum frutescens L.) Yang Bergejala Antraknosa Dari Lahan Pertanian Di Dusun Jeruk - Rahmawati, Widya Anggraeni Elvi Rusmiyanto PW, (Universitas Tanjungpura, 2019)
Anthracnose is a disease that often attacks cayenne pepper (Capsicum frutescens L). This study aims to determine the species of fungus from the fruit of cayenne pepper with anthracnose symptoms. Fungal isolation was carried out using the direct plating method and fungal identification was carried out by observing the macromorphological and micromorphological characteristics of the fungi. The results showed that two fungal species were obtained, namely Colletotrichum sp (WA2) and Idriella sp. (WA3). Colletotrichum sp. (WA2) is a pathogenic fungus that causes anthracnose and Idriella sp (WA3) is a saprophytic fungus, but it is also known to be capable of being a pathogenic fungus.